Chronic patient care at North West Province clinics - Claire van Deventer; Ian Couper; Nontsikelelo Sondzaba (AOSIS, 2009)
Background: Chronic illnesses are a significant burden to the health services in South Africa. There is a specific national health plan whereby chronically ill patients who are acceptably controlled should be managed at clinic level. The perception has emerged that the management of primary care has not been optimal in the Southern District of the North West Province. This provided the motivation to initiate this research, namely consideration of chronic patient care at clinics in the North West Province of South Africa. Method: A cross-sectional descriptive study was carried out at four randomly selected clinics covering four sub-districts in the Southern District (North West Province). This was done using charts and registers at the clinics. Inclusion criteria were patients older than 18, and presenting with the following chronic illnesses: asthma/chronic obstructive airways disease (COAD), hypertension, diabetes and epilepsy. The major focus areas were the regular assessment of the patients, the level of control of the illness and the use of the Essential Drugs List and Standard Treatment Guidelines (EDL/STG). Results: In the cases of all the chronic illnesses it was found that regular assessments were poorly done, with asthma (peak flow measurements) being the most poorly done. Control was generally less than 50% for all the illnesses, although the EDL was followed fairly well by the personnel at the clinics. Conclusion: In the light of the burden of chronic illness the results give cause for great concern about the quality of care for chronically ill patients, and reasons were sought for some of the poor results. A subsequent decision was taken to carry out comprehensive quality improvement projects on each of the illnesses over the following five years.